THU0138 The Corrona International Rheumatoid Arthritis Registry: Variations in Disease Activity and Management Across Participating Regions. (23rd January 2014) - Pappas, D. A.; Lampl, K.; Kremer, J. M.; Nyberg, F.; Gibofsky, A.; Ho, M.; Horne, L.; Saunders, K.; Onofrei, A. U.; Greenberg, J. D.
Abstract : Background: To date, there is no multinational Rheumatoid Arthritis (RA) registry uniformly collecting longitudinal data. The CORRONA International (CI) registry was developed to address this need. Objectives: To explore variations in RA disease (dx) activity and drug utilization across regions participating in CI RA registry and the US CORRONA RA registry. Methods: The CI registry, launched in September 2011, is a multi-center, longitudinal, observational registry collecting data on demographics, lifestyle characteristics, anthropometry, medication exposures, adverse events and toxicities from rheumatologists and RA patients (pts) at regular clinical encounters. Adult RA pts have been enrolled in 10 countries in 3 regions [Eastern Europe: Poland, Czech Republic, Hungary, Romania, Russia, Ukraine; Latin America: Mexico, Brazil, Argentina; Asia: India]. We present baseline descriptive data including: variations in biologic and DMARD utilization, dx activity and functionality across the regions participating in both registries. Results: As of Nov 2012, 4042 patients had been enrolled in CI. Table 1 shows variations in dx characteristics among the CI regions and the USA. In general, dx activity is higher but functionality and biologic drug utilization is lower in CI regions compared to USA. Biologics use is still very rare in India. Conclusions: The CI registry reveals differences in the management of RA across different global regions. The ongoing recruitment and follow-up of more pts will enable association studies between therapeutic variations and disease outcomes. Acknowledgements: Funding for this study was provided by CORRONA (study sponsor), from a development and subscription agreement/contract with AstraZeneca. Disclosure of Interest: D. Pappas Employee of: Columbia University, Paid instructor for: Novartis, K. Lampl Employee of: AstraZeneca, J. Kremer Shareholder of: CORRONA, Inc., Employee of: CORRONA, Inc., F. Nyberg Employee of: AstraZeneca, A. Gibofsky Consultant for: AstraZeneca, M. Ho Employee of: AstraZeneca, L. Horne Shareholder of: AstraZeneca, Employee of: AstraZeneca, K. Saunders Employee of: CORRONA, Inc., A. Onofrei Employee of: University of Massachusetts, J. Greenberg Shareholder of: CORRONA, Inc., Consultant for: AstraZeneca, CORRONA, Novartis, Pfizer